Pengaruh Resiko Bisnis, Profitabilitas, Struktur Aktiva, dan Ukuran Perusahaan terhadap Struktur Modal pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2010-2014 - Aprili, Resti; , Fauzan, SE, Ak, M.Si (2016)
This research examined the effect of business risk, profitability, asset structure, firm size to capital structure in the manufactured companies listed on the Indonesia Stock Exchange in 2010-2014. The research sample included 48 companies selected through the purposive sampling. This research uses secondary data that have passed the test and analyzed using the classical assumptions of multiple linear regression analysis. Analytical results for the first dependent variable showed that the profitability and firm size influence the capital structure. While business risk and asset structure has no effect on capital structure. Keywords: business risk, profitability, asset structure, firm size and capital structure.